A novel interface layer for inverted perovskite solar cells fabricated in ambient air under high humidity conditions. (October 2020) - Gokdemir Choi, Fatma Pinar; Moeini Alishah, Hamed; Bozar, Sinem; Doyranli, Ceylan; Koyuncu, Sermet; San, Nevim; Kahveci, Cihangir; Cantürk Rodop, Macide; Arvas, Melih Besir; Gencten, Metin; Sahin, Yucel; Gunes, Serap
Highlights: Synthesis and characterization of a novel benzotriazol based small molecule (BTBT). Evaluation of BTBT molecule as an interlayer in perovskite solar cells. Low temperature fabrication route using inverted perovskite solar cell geometry. Achievement of high efficiencies without glove box conditions under high humidity. Improvement of efficiency using BTBT as an interlayer between ITO and PEDOT:PSS. Abstract: A novel benzotriazol based small molecule (2-hexyl-4, 7-bis(5′-hexyl-2, 2′-bithien-5-yl)-2H-1, 2, 3-benzotriazole) "BTBT" was synthesized by Suzuki coupling reaction and was successfully employed in planar inverted perovskite solar cells with ITO/BTBT/PEDOT:PSS/CH3 NH3 PbI3-x Clx /PCBM/Al configuration. Fabrication processes, including the spin coating of the perovskite layer, were performed in ambient air, under high humidity conditions (>60%). BTBT/PEDOT:PSS bilayer notably improved the power conversion efficiencies (PCE) from 9.65% to 11.6%, which corresponds to an increase of 20%.